Analytical Concordance of PD-L1 Assays Utilizing Antibodies From FDA-Approved Diagnostics in Advanced Cancers: A Systematic Literature Review. (2021) - Prince, Emily A.; Sanzari, Jenine K.; Pandya, Dimple; Huron, David; Edwards, Robin
Abstract : PURPOSE: Four programmed death ligand 1 (PD-L1) immunohistochemistry assays (28-8, 22C3, SP263, and SP142) have been approved for use by the US Food and Drug Administration (FDA). Analytical concordance between these assays has been evaluated in multiple studies. This systematic review included studies that investigated the analytical concordance of immunohistochemistry assays utilizing two or more PD-L1 antibodies from FDA-approved diagnostics for evaluation of PD-L1 expression on tumor or immune cells across a range of tumor types and algorithms. METHODS: Literature searches were conducted in MEDLINE (via PubMed) and EMBASE to identify studies published between January 1, 2010, and March 31, 2019, that evaluated analytical concordance between two or more assays based on antibodies from FDA-approved assays. Proceedings of key oncology and pathology congresses that took place between January 2016 and March 2019 were searched for abstracts of studies evaluating PD-L1 assay concordance. RESULTS: A total of 42 studies across a range of tumor types met the selection criteria. Concordance between 28-8-, 22C3-, and SP263-based assays in lung cancer, urothelial carcinoma, and squamous cell carcinoma of the head and neck was high when used to assess PD-L1 expression on tumor cells (TCs). SP142-based assays had overall low concordance with other approved assays when used to assess PD-L1 expression on TCs. Analytical concordance for assessment of PD-L1 expression on immune cells was variable and generally lower than for PD-L1 expression on TCs. CONCLUSION: A large body of evidence supports the potential interchangeability of 28-8-, 22C3-, and SP263-based assays for the assessment of PD-L1 expression on TCs in lung cancer. Further studies are required in tumor types for which less evidence is available.